A decision support system for verifying the quality of application software code (MCIT: Proceedings of International scientific and practical conference, 2023)
The proposed architecture of the decision support system for quality control of software code of applied codebases. The proposed approach is modular and applicable to most software development projects. The proposed system allows deriving empirical rules for long-term software development and maintenance.